Congenital Erythropoietin Porphyria (CEP) ? A Case of Necrotic Scleritis - , Ashraf Ali Tayyab, Sehbaz Aslam, Muhammad Imran, Syed Ahmer Hussain (Pakistan Journal of Ophthalmology, 2018)
Purpose: To discuss a case of bilateral temporal sclera necrosis leading to scleral perforation. Material and Methods: This is an observational case report in an institutional setting, reporting an unusual case. A 26 years old young man, farmer by occupation presented to Nishtar Hospital Multan with pain and photophobia in his left eye. Examination showed bilateral involvement of temporal sclera leading to sclera perforation. The visual acuity was 20/20 on log Mar in both eyes. The pupils were reactive to light and Intra-ocular pressure was 14mmHg and 12 mmHg in right and left eye respectively. Dilated fundus examination was found to be normal with Cup – Disc ratio of 0.3 both eyes. Investigation (CBC, peripheral blood film, CRP, Rh factor, X-ray chest, biochemical analysis of specimen) led to unusual case of Gunther’s disease also known as congenital erythropoietin porphyria 3.